Dversifikasi Kue Kering Kekinian Berbahan Baku Beras Merah Lokal dan Sagu - Noor Mirad Sari; Violet Violet; Khairun Nisa; Ayu Manipa (Universitas Lambung Mangkurat, 2022)
The Yasinan Arraudah group consists of women who work as traders, catering services, and housewives. The impact of the Covid-19 pandemic has affected partners, namely a decrease in sales turnover until the closure of businesses for members who work as traders or catering services. The implementation team of the Community Partnership Program provides the right solution for business opportunities in the new normal era, namely making healthy pastries made from brown rice flour and sago flour. The selection of local brown rice flour and sago flour to support the government's efforts in accelerating the diversification of food consumption based on local resources and reducing dependence on wheat flour. The problem faced by partners is the lack of knowledge about how to make modern pastries from local brown rice and sago which is healthy and hygienic and does not have the equipment, availability of raw materials, packaging methods and product marketing methods. The method of activity is in the form of counseling, training in making pastries, assistance to activity partners and program evaluation. The results of the counseling and training activities showed that 80% of the participants were able to make modern pastries made from brown rice and sago, namely Nastar Beras Merah, Cookies Susu Wijen, Kuker Sagu, and Selai Cookies. The outputs produced in the Community Partnership Program activities are in the form of contemporary pastries, publications in mass media, activity videos on YouTube and scientific articles.Keywords: contemporary pastries, food diversification, local brown rice, and sago